THE COOPERATION OF THE WORDS IN SAID NURSI’S WORKS - Adnan ARSLAN (Fırat University, 2021)
Bediuzzaman Said Nursî is one of the prominent Islamic scholars of the last century, who was educated in the Anatolian science tradition. Although there are many factors in which the treatises he has written have a great interest, it is understood that this countenance is related to the literary language of the treaties. Said Nursî pays attention to repeating the words with the same or similar meaning and reinforcing the meaning in the treatises he wrote. These repetitions can have many purposes. This study emphasized what he intended with these repetitions he made in his treaties. As it is seen, these word repetitions expresses a silent resistance of the author against the simplification approaches in the language which started with the introduction and peaked with the transition to the republic. The author wanted to keep the Ottoman Turkish language alive in the next generations in the first degree by the Muslims who had written the words of Anatolian Muslims through faith and reinforcement of faith. In this respect, it can be said that close repetitive word repetitions in the narratives are manifestations of not only religious but also language-oriented anxiety.